Self-efficacy, perceived social support and psychological Adjustment in international students of Universiti Utara Malaysia - Muhammad Fazlee Syam, Abdullah (2013)
Due to the globalization of the economy, political and society give an impact on Malaysian higher education institutions, especially public universities. The Ministry of Higher Education Malaysia had a strategy on globalizing local education through increasing the number of international students in Malaysia. While adjusting to a new culture, many of international students struggle to do so. The role of self-efficacy, perceived social support and psychological adjustment is crucial because of the differences in academic and cultural challenges when they are in Malaysia. Furthermore, the current study analysed the relationship between self-efficacy, perceived social support and psychological adjustment. A total of 150 international students from various country and nation in Universiti Utara Malaysia (UUM) completed the questionnaire survey. As hypothesized, independent variables of the study; self-efficacy and perceived social support significantly related with psychological adjustment. Implication on the findings and future research on international students are discussed.